Solvability of Fractional Differential Inclusion with a Generalized Caputo Derivative. (28th December 2020) - Nabil, Tamer
Abstract : This paper is devoted to the investigation of a kind of generalized Caputo semilinear fractional differential inclusions with deviated-advanced nonlocal conditions. Solvability of the problem is established by means of the Leray-Schauder's alternative approach with the help of the Lagrange mean-value classical theorem. Finally, some examples are given to delineate the efficient of theoretical results.